A STIRPAT model of sectoral CO2 emissions at the county scale - Sztukowski, John, author; Zahran, Sammy, advisor; Peek, Lori, committee member; Betsill, Michele, committee member (Colorado State University. Libraries, 2010)
Background: The scientific community agrees that the principal cause of increased surface temperature globally is the accumulation of greenhouse gases (GHGs) in the atmosphere, with carbon dioxide (CO2) emissions from fossil fuel combustion being most important among GHGs. Objectives: To analyze the spatial correspondences between CO2 emissions and anthropogenic variables of population, affluence, and technology in the United States. Methods: Ordinary least squares regression and spatial analytical techniques are used to analyze variation in CO2 emissions based on a modified version of the STIRPAT model. The unit of analysis is the county, with 3108 counties in the contiguous United States analyzed. The CO2 emissions of multiple sectors are analyzed as a function of total county population, income per capita, and climatic variation. Results: Population has a proportional relationship, the strongest association, with CO2 emissions. Affluence has a positive relationship with CO2 emissions with an attainable Environmental Kuznets Curve for the residential sector and total CO2 emissions. Climate, including average winter and summer season temperature, has a positive relationship with total CO2 emissions, although it has a negative relationship with the residential and commercial sectors of CO2 emissions. Technology acts as the residual in the model, accounting for net-positive and net-negative technology. Conclusion: Population growth, and to a smaller extent economic growth, are the driving forces of CO2 at the local level. These findings are consistent with global STIRPAT models. An increase in winter or summer temperature further exacerbates CO2 emissions. Understanding the relationships between these anthropogenic variables and environmental impacts at the local scale is a crucial step in the process of formulating mitigation strategies aimed at reducing CO2 emissions in the US.
Keywords: CO2; EKC; environment; population; regression; STIRPAT